Aerosol jet printed strain sensor : simulation studies analyzing the effect of dimension and design on performance (September 2018) - Agarwala, Shweta (2018)
The 3-D printing has been gaining widespread attention for electronic applications. Aerosol jet printing has emerged as a powerful technique to print new-age sensors and devices on various substrates. In this paper, we use simulation studies to optimize the dimensions and design of aerosol jet printed strain sensor for a good performance. Physical dimensions such as the end loop length, number of grids, grid line width, gauge length, and five different sensor designs are simulated to study their effect on the performance of the strain sensor. This paper helps to identify the factors that affect the sensitivity and gauge factor of the flexible strain sensor fabricated using aerosol jet printing technology.